Iontophoretic Transport of Local Anesthesia: A Literature Review - Nafeesa Tabassum, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim:This study aimed to comprehensively review the literature about the use of iontophoresis for the transportation of local anesthesia to better understand the feasibility of such technique and its benefits compared to other delivery systems. In addition, in the current review we present the challenges compromising the use of this drug delivery system in this area. Material and Methods: This is a literature review which aimed to screen old as well as very recent literature on the technique, methodology, clinical findings, influencing factors of local anesthetics iontophoresis, thus PubMed electronic databases were screened. Indexed articles during the time period extending between 1977 and 2021 were tentatively reviewed. This review was registered by and it only included articles written in English. Research studies conducted in vitro or on animals were excluded in addition to case studies, case series, and pilot studies. Articles that included major forms of bias were also excluded. Pubmed database was screened using the following Mesh terms: Anesthetics, Local / administration & dosage*, Epinephrine / administration & dosage, Ethanol / pharmacology, Humans, Iontophoresis*, Lidocaine / administration & dosage, Regional Blood Flow, Skin / blood supply, Skin / drug effects*Skin / metabolism. Results: A total of 89 studies were screened for possible inclusion after searching for the above mesh terms in PubMed. Eventually, 16 articles were included in this review where 2 studies were related to iontophoretic anesthesia of the ear, 6 were related to skin anesthesia, and 7 related to the oral cavity. The other three studies compared the use of local anesthesia mediated by iontophoresis to other approaches and the change in dosing requirements following iontophoresis administration of local anesthetics.